PENGARUH NILAI TUKAR MATA UANG ASING (KURS) DAN TINGKAT BUNGA (BI RATE) TERHADAP INDEKS HARGA SAHAM GABUNGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2005-2019 - Hanita Destia; Syapsan Syapsan; Richard Rahmat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of foreign currency exchange rates (exchange rates) and interest rates (bi rate) on the composite stock price index listed on the Indonesian stock exchange. The data used are time series data for the period 2005-2019. The analytical method used is multiple linear regression. The results of the research obtained are partially the exchange rate has a significant positive effect on the composite stock price index (IHSG) and the bi rate has a significant negative effect on the Composite Stock Price Index (IHSG) by adjusting R square 78.7% of the variable stock price index (IHSG). In this study, it can be influenced by the 2 independent variables, bi rate and exchange rate, while the remaining 21.3% is influenced by other factors outside the independent variable.Keywords: Kurs, Bi Rate, IHSG